Agro-ecological zonation of canola cultivation in Ardebil Plain - Bhroz Sobhani; fatemeh nasiri (تحقیقات کاربردی علوم جغرافیایی)
Recognition and determination of ecological susceptible regions for proper bedding is importance and vital affair for regional planning and specially agriculture part. Climate and topography are main environmental components which altitude and cultivation product generation capability are depend their in every region.  So , studying of effective climate factors and elements on agriculture have special importance. In current study , in order to agriculture ecological homogeneous geographical regions determination ; satellite images of Geographical Information Bases (GIS) were used which they are provider of new horizon and dimensions for effective discovering and fields resources management and we try to show Rapeseed cultivation ecological zoning usage development by combining modern tools , instruments and methods at Ardebil plain region. In order to recognition of mentioned susceptible regions in studied case climate data statistics were used that they include ; temperature degree , precipitation, relative humidity and environmental capability data such as ; inclination, height and multi-criteria decision making based on Analysis of Networks Process(ANP). Then layers were prepared by weighting and according to criteria and they were combined and also layers overlapping were done on GIS environment and ultimate layer of fields proportion was prepared for Rapeseed cultivation. Based on results analysis , studied region fields for Rapeseed cultivation include 33/38% without limitation ; 02/10% of fields with low limitation; 96/33% with medium limitation ; 71/17% of fields with high limitation